The Coming Democracy: New Rules for Running a New World - FLORINI, Ann (Institutional Knowledge at Singapore Management University, 2003)
National governments are proving ill-equipped to manage an increasingly complicated portfolio of global problems. In The Coming Democracy, political analyst Ann FLORINI sets forth a compelling new paradigm for transnational governance. It is based on the concept of "transparency," the idea that the free flow of information --on topics ranging from corporate and government behavior to nuclear proliferation to biodiversity protection --provides powerful ways to hold decisionmakers accountable and to give ordinary people meaningful voice in shaping the policies that affect them. Thanks to dramatic breakthroughs in information technology over the past decade, such transparency is now possible on a global scale. FLORINI offers a clear and comprehensive assessment of the possibilities for using transparency to develop effective approaches to transnational governance. She shows how this new form of governance offers real hope for managing global problems, and provides a compelling scenario that demonstrates how existing conventions and institutions can lead the way in the evolution of a better system of global governance.